Control de inventarios en almacén de Agroquímicos Comercial Rocío, Babahoyo, periodo 2020-2021. - Mejía Coca, Roció Emperatriz (2022)
The present case study was carried out in the Rocío commercial, in the city of Babahoyo, this organization is dedicated to the commercialization of agricultural products. For this, the following objective was set, to analyze the control of inventories in the Comercial Rocío agrochemical warehouse, through documentary review to avoid losses. It was framed in the Audit and Control research subline. Its methodology was qualitative-quantitative with a retrospective approach, its population was made up of the manager and the workers, as a technique the analysis of inventory documents, an interview and a survey were used. Its results showed that the commercial handles an inventory manually, its rotation is given annually and in this case there are difficulties for the dispatch or control of new products and those that are about to expire. It was concluded that it is necessary to have an exhaustive analysis of the importance of inventory control, this in turn ensures that you acquire more accurate and efficient information for the development of the company and it is recommended that the company carry out a more continuous review of its inventories. so that they can have knowledge about how the stay of the products is handled.